Transformation of learning and teaching in rehabilitation sciences: A case study from South Africa, in Human Functioning - Visser, Monique (Technology and Health Book Series, 2022)
This is the second book in the 'Health, Functioning and Technology' series. The focus of this book is on teaching, learning and assessment in rehabilitation education within the African context. The primary contributors to the book are authors from occupational therapy, physiotherapy and speech-language therapy in South Africa. The authors discuss local contextual drivers for renewing rehabilitation professions curricula that support graduates in becoming competent, socially accountable, and dynamic. The foundational element of the chapters in the book is the African context and evidence-informed educational practice. We include the impact of the COVID-19 pandemic on teaching, learning, student support and the integration of technology to assist in achieving the goals of the curricula. Through the different themes of transformative learning, curriculum renewal, technology for learning and clinical training key topics are covered on responsive curricula, leadership, interprofessional education, clinical competence, critical consciousness, peer teaching and learning, learning technologies, student support and emergency remote teaching and learning.